Wheat yield gaps and its implications on food security in East Africa: a comprehensive analysis of factors and consequences - Bacha Gebissa Negeri; Bai Xiuguang (Cogent Food & Agriculture)
Wheat is a cereal grain that is the most widely grown and consumed staple crop in the world. However, the productivity of wheat in East Africa is low compared to the world production level. This study review provides a comprehensive analysis of the factors contributing to wheat yield gaps in East Africa from 2017 to 2025 published papers and explores the implications for agricultural productivity and food security in the region. Despite the region’s potential for wheat cultivation, yield gaps remain significant, with production levels falling short of their potential. Key factors affecting include soil fertility, climate variability, limited access to modern farming techniques, insufficient extension services, inadequate infrastructure, and socioeconomic constraints such as access to credit and education. The analysis draws data from various countries in East Africa, highlighting the subtle relationship between these factors and their cumulative impact on wheat production and productivity. The study review emphasizes the need for a multifaceted approach to enhance wheat productivity, with implications for improving food security, livelihoods, and regional agricultural resilience. Furthermore, policymakers must include the key drivers of wheat yield gaps and approaches to bridge the yield gaps in East Africa to increase the productivity of wheat and sustainable livelihoods for farmers across the region.